1988
DOI: 10.1039/c39880001579
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical fate of (2S,4R)- and (2S,4S)-[4-2H]methionine in nocardicin A biosynthesis

Abstract: The incorporation of (2S,4R)and (2S,4S)-[4-*H]methionine into nocardicin A proceeds with inversion of config u ration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…66A). 615,619,620 Feeding of racemic [2-13 C, 15 N]-pHPG demonstrated that pHPG provides the nitrogen atoms of both the b-lactam and of the oxime in nocardicin A. 621 Employing L-[2-3 H, 1-14 C]-pHPG, it was found that tritium is not incorporated into the 5-position of nocardicin A.…”
Section: Nocardicin Biosynthesismentioning
confidence: 99%
“…66A). 615,619,620 Feeding of racemic [2-13 C, 15 N]-pHPG demonstrated that pHPG provides the nitrogen atoms of both the b-lactam and of the oxime in nocardicin A. 621 Employing L-[2-3 H, 1-14 C]-pHPG, it was found that tritium is not incorporated into the 5-position of nocardicin A.…”
Section: Nocardicin Biosynthesismentioning
confidence: 99%
“…2). The stereochemical course of side chain attachment was shown to be inversion through the incorporation of methionine stereospecifically deuterated at C-4 (13). This configurational outcome parallels the stereochemistry of addition of the 3-aminopropyl moiety derived from decarboxylated S-adenosylmethionine (AdoMet) 1 operative in the biosynthesis of the polyamines (14 -16), as well as more conventional methyltransferases (17,18), suggesting a role for AdoMet in nocardicin A biosynthesis in vivo.…”
mentioning
confidence: 88%
“…Magnetic susceptibility measurements (SQUID) on microcrystalline samples of 2 (gcfr (300 K) = 2.02 pB, peff (5 K) = 1.73 fiB) indicate that 2 has a larger ground-state orbital contribution than vanadyl (V02+) complexes. 1,11 The IR spectrum of 2 shows a band at 934 cm'1 (t'cr-o)l isotopic labeling12 using 17,1802 resulted in additional absorptions at 917 and 900 cm'1. A crystallographic study shows that 2 adopts a typical piano-stool geometry with very short Cr-07,l2a (1.58 (2) A) and and 2.375 (5) A) distances (Figure 2).…”
mentioning
confidence: 99%
“…Careful addition of Br2 to solutions of 2 as well as electrochemical reduction of 2 at -140 mV results in concomitant deoxygenation to give 1. In the thermal conversions (toluene) of 2 to 1,180-labeling studies in conjunction with GC-MS analyses14 indicate that the final oxygen-containing species are polychromatcs (50%), "Cp*OH" (20%), water (10%), (11) Gardner, C. D.; Kendrick, J.; Lambert, P.; Mabbs, F. E.; Hillier, I. H. Inorg. Chem.…”
mentioning
confidence: 99%
See 1 more Smart Citation